Keragaman Fenotipe dan Genetik Beberapa Plasma Nutfah Ubi Kayu (Manihot Esculenta L.) Lokal Papua - Theresia Tan; Yohanes A. Mustamu; Putri Surinawati; Imam Widodo; Yohanes Sriyadi Budiyanto (Agrotek, 2023)
This study aimed to 1) predict the phenotypic diversity between local Papuan cassava genotypes, 2) determine the characters that make the greatest contribution to diversity and 3) determine the characters that have the same degree of similarity. This research was carried out from April 2020 to March 2021 in the Manggoapi experimental garden, Faculty of Agriculture, University of Papua. This research was an observational study, and used purposive sampling method in the form of qualitative research without spatial planning, as well as descriptive analysis techniques to describe the data obtained. The cassava used in this study totaled ten genotypes without control and replication treatments. The variables observed consisted of morphological characters combined with agronomic characters, which included 46 morpho-agronomic characters. Based on the results of the study it can be concluded that 1) there was broad and narrow phenotypic diversity between 10 local Papuan cassava genotypes from the UNIPA Genetics and Plant Breeding Laboratory collection, broad characters were more dominant than narrow characters, because the cassava observed was more influenced by genetics than environment. (2) The eigenvalues of the morpho-agronomic characters of the 10 local Papuan cassava genotypes ranged from 1.614-10.687 with a character contribution of 98.041% indicating that the morpho-argronomic characters made a large contribution to the 10 observed Papuan local cassava genotypes. (3) 10 local Papuan cassava genotypes collected by the Genetics and Plant Breeding Laboratory of UNIPA which were analyzed using clusters obtained results with a coefficient value of 65%, there was the same similarity between the Amban 3 and Amban 4 genotypes, as well as for the Amban 5 and Amban 8 genotypes.